Macro-anatomical investigations on the skeletons of porcupine (Hystrix cristata) - I. Ossa membri thoracici - Yilmaz, S; Ozkan, ZE; Ozdemir, D (Scientific Technical Research Council Turkey, 1998)
In this study, two porcupines (Hystrix cristata) were used to investigate the bones of fore limb. It was observed that the area of fossa supraspinata (54.7%) was larger than that of fossa infraspinata (45.3%). Processus hamatus and processus suprahamatus were present and processus coracoideus was well developed. Tuberculum majus elevated slightly over the level of caput humeri. Tuberositas deltoidea was well developed and tuberositas teres major et minor were prominent. Foramen supratrochleare, crista epicondyli lateralis and sulcus ulnaris were present. Spatium interosseum antebrachii was present and on the facies of every two bones towards the spatium a deep groove was seen. Lateral and medial processus styloideus were well developed. Four proximal and four distal ossa carpi and five ossa metacarpalia were determined.
Keywords: Hystrix cristata; porcupine; ossa membri thoracici